2010
DOI: 10.4049/jimmunol.0903401
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Programmed Death-1 in Young (New Zealand Black × New Zealand White)F1 Mice Promotes the Activity of Suppressive CD8+ T Cells That Protect from Lupus-Like Disease

Abstract: The programmed death-1 (PD-1)/programmed death-1 ligand 1 (PD-L1) pathway regulates both stimulatory and inhibitory signals. In some conditions, PD-1/PD-L1 inhibits T and B cell activation, induces anergy, and reduces cytotoxicity in CD8+ T cells. In other conditions, PD-l/PD-L1 has costimulatory effects on T cells. We recently showed that induction of suppressive CD8+Foxp3+ T cells by immune tolerance of lupus-prone (New Zealand black × New Zealand white)F1 (BWF1) mice with the anti-DNA Ig-based peptide pCons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 30 publications
(39 reference statements)
0
26
1
Order By: Relevance
“…This positive effect was difficult to reconcile with the high auto-Ab titers and the lupus symptoms observed in PD-1 knockout mice (21,31). In our study, T regs expressing PD-1 ligands acted negatively on autoreactive PD-1 + B cells, explaining the phenotype of PD-1-deficient mice (21,38). This is no contradiction because T regs will operate only in responses against self-antigens and prevail over the positive effect on follicular Th cells.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…This positive effect was difficult to reconcile with the high auto-Ab titers and the lupus symptoms observed in PD-1 knockout mice (21,31). In our study, T regs expressing PD-1 ligands acted negatively on autoreactive PD-1 + B cells, explaining the phenotype of PD-1-deficient mice (21,38). This is no contradiction because T regs will operate only in responses against self-antigens and prevail over the positive effect on follicular Th cells.…”
Section: Discussioncontrasting
confidence: 61%
“…Here we show that T regs control autoreactive B cells specific for tissue auto-Ag through the suppressive surface molecule PD-1. Others have previously shown that follicular Th cells express high amounts of PD-1 (37) and that PD-1 inhibits Th cells (38), suggesting that indirect B-cell suppression, by curbing help for auto-Ab production, may play a role. Cell culture studies by others had hinted at the possibility of direct suppression (10)(11)(12), but providing in vivo evidence required an experimental system by which either the direct or the indirect route of suppression could be incapacitated.…”
Section: Discussionmentioning
confidence: 99%
“…B7-1 cross-linking activates CD4 + T cells and increases T cell proinflammatory cytokine production (48). Disrupting PD-L1-PD-1 interaction by anti-PD-1 Ab protects lupus-like nephritis in NZB/W F1 mice by either reducing CD4 + PD-1 + T cells (49) or promoting suppressor CD8 + T cell activity (50). However, these anti-PD-1 blocking experiments are long term studies and the results do not necessarily apply to the current short-term anti-GBM model.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with our current results, antibodies against PD-1 might accelerate the severity of lupus in vivo by blocking the biological function of the PD-1 signaling pathway. Controversially, in vivo blockade of PD-1 receptor in a lupus murine model (NZB/WF1) has been shown to delay the disease progression [3436], and might, owing to the high affinity and doses of commercial PD-1 antibodies administered to mice, result in the dissolution of T cells instead of the inhibition of T cells function.…”
Section: Discussionmentioning
confidence: 99%